SOCIAL SUPPORT OF MOTHERHOOD AND CHILDHOOD IN URSR AND FOREIGN COUNTRIES AT THE BEGINNING OF THE 20TH CENTURY: LEGAL ASPECTS - Stynska, Victoriya V. (Educological discourse, 2015)
The main approaches of social support of motherhood and childhood in URSR and foreign countries at the beginning of the 20th century are analyzed in the article. The development of law base of child defence is observed , the main demands that are connected with social support of motherhood and childhood, the implementation of constitutional defence of rights and freedom of childhood, the improvement of conditions for their upbringing and development, the struggle with homelessness, the defence of work and health of mother and child are described in the article.